Paradigma Kurikulum Berbasis Cinta: Upaya Membangun Karakter Islami dan Humanis - Aliyya, Salwa Maysa; Apsari, Witri Kartika; Maolani, Ogi; Parhan, Muhamad (Program Studi Pendidikan Agama Islam Fakultas Ilmu Tarbiyah dan Keguruan UNSIQ Jawa Tengah, 2025)
This study analyzes the paradigm of the Love-Based Curriculum (LBC) as a learning approach in Islamic education that emphasizes the development of Islamic and humanistic character. The method employed is a literature study with descriptive analysis, examining the theoretical foundations, concepts, values, and implementation of LBC in the context of contemporary education. The main focus of the study is how LBC integrates elements of compassion, empathy, and tolerance into the learning process so that students can be shaped into faithful individuals with noble character and strong emotional intelligence in facing social and global challenges. The findings indicate that LBC makes a significant contribution to character development; however, its implementation still encounters several obstacles, particularly the limited understanding of teachers, lack of policy support, and insufficient resources. This study recommends strengthening educators’ capacity through structured training and providing adequate resources to optimize the implementation of LBC. These findings highlight the importance of Islamic education that balances cognitive, affective, and spiritual aspects as the foundation for developing a high-quality and adaptive Islamic generation in the modern era.